Identifying the molecular basis of Jinhong tablets against chronic superficial gastritis via chemical profile identification and symptom-guided network pharmacology analysis - Danfeng Shi; Lingxian Liu; Haibo Li; Dabo Pan; Xiaojun Yao; Wei Xiao; Xinsheng Yao; Yang Yu (Elsevier, 2022)
Chronic superficial gastritis (CSG) is a common disease of the digestive system that possesses a serious pathogenesis. Jinhong tablet (JHT), a traditional Chinese medicine (TCM) prescription, exerts therapeutic effects against CSG. However, the molecular basis of its therapeutic effect has not been clarified. Herein, we employed ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q/TOF-MS) based chemical profile identification to determine the chemical components in JHT. Further, we applied network pharmacology to illustrate its molecular mechanisms. A total of 96 chemical constituents were identified in JHT, 31 of which were confirmed using reference standards. Based on the bioinformatics analysis using the symptom-guided pharmacological networks of "chi," "blood," "pain," and "inflammation," and target screening through the interaction probabilities between compounds and targets, matrix metalloproteinase 2 (MMP2), dopamine d2 receptor (DRD2), and Aldo-keto reductase family 1 member B1 (AKR1B1) were identified as key targets in the therapeutic effect exhibited by JHT against CSG. Moreover, according to the inhibitory activities presented in the literature and binding mode analysis, the structural types of alkaloids, flavonoids, organic acids, including chlorogenic acid (10), caffeic acid (13), (−)-corydalmine (33), (−)-isocorypalmine (36), isochlorogenic acid C (38), isochlorogenic acid A (41), quercetin-3-O-α-l-rhamnoside (42), isochlorogenic acid B (47), quercetin (63), and kaempferol (70) tended to show remarkable activities against CSG. Owing to the above findings, we systematically identified the chemical components of JHT and revealed its molecular mechanisms based on the symptoms associated with CSG.